Newly qualified nurses' experiences of organizational and psychosocial working environments in hospitals - an occupational health theoretical perspective - Frydenlund, Markus Hagen; Johannessen, Berit; Gundersen, Ellen Dahl (Nordisk Tidsskrift for Helseforskning, 2024)
A considerable amount of newly qualified nurses working at Norwegian hospitals are seeking alternative employment. The working environments affect nurses' occupational health and their desire to remain at their jobs. There is little up-to-date knowledge concerning the working environment in Norwegian hospitals.   The purpose of this study was to gain knowledge about newly qualified nurses' experiences of the organizational and psychosocial working environments in somatic wards, using an occupational health theoretical perspective. The study had a qualitative design, with data collection from semi-structured individual interviews with nine newly qualified nurses. The data material was analyzed based on Malterud's systematic text condensation. The nurses experienced that the working environment was characterized by high workloads, role challenges, and a discrepancy between effort and reward. Furthermore, they described being a newly qualified nurse as professionally challenging. They experienced a high degree of social support from colleagues, but their experiences with management were varied. The findings suggest a discrepancy between job demands and job resources, which, according to theories about occupational health, can lead to physical and psychological stress. Strengthening nurses' resources to meet job demands will be important in order to lessen the consequences of job demands, promote occupational health and hopefully contribute to keeping more nurses in work.
Keywords: Working environment; occupational health; organizational; psychosocial; hospital